Tolerance to high temperature in F-5 inbred lines of tomato - Santos, Lucas S. [UNESP]; Melo, Roberto A.; Santos, Paulo R.; Carvalho Filho, José L. S.; Menezes, Dimas (Assoc Brasileira Horticultura, 2014)
High temperatures in the growing tomato have caused a reduction in fruit set and consequently productivity. This work aimed to evaluate F-5 lines of tomato to fruit set and high temperature tolerance in two culture environments. Two experiments were carried out, one in cultivation in greenhouse and the other in the field conditions, from February to June 2012. We evaluated 20 lines F-5 of tomato, originating from the segregation of hybrid SE 1055 F-1, developed for the hot and humid conditions, with resistance to Fusarium oxysporum f.sp. lycopersici race 2, the tomato mosaic virus (ToMV), the Verticilium dahliae and geminivirus (TYLCV) and the control cultivar Yoshimatsu and own hybrid SE 1055 F1. The experiment was performed in a randomized blocks design with 22 treatments, four replications and plots with two plants. We evaluated the total number of fruits per plant (NTF/PL), mass of unmarketable fruits per plant (MFNC/PL), fruit set (PEG), mass of marketable fruits per plant (MFC/PL) and yield of marketable fruits (REND). In the greenhouse were recorded higher temperatures and lower luminosity than in field cultivation. Lines 08, 12 and 13 showed higher fruit set in a greenhouse, being more suitable for cultivation at high temperatures. In the field, the lines 06 and 08 showed that marketable fruit production did not differ from 'Yoshimatsu'. Comparing the field experiment average with the average of greenhouse, a higher fruit set and a higher mass of marketable fruits per plant was achieved in field.

As temperaturas elevadas nas áreas de cultivo de tomateiro têm causado redução no pegamento de frutos e consequentemente na produtividade. Este trabalho teve como objetivo avaliar linhagens F5 de tomateiro quanto ao pegamento de frutos e tolerância a altas temperaturas em dois ambientes de cultivo. Foram conduzidos dois experimentos, um no cultivo em casa de vegetação e outro no campo, de fevereiro a junho de 2012. Foram avaliadas 20 linhagens F5 de tomateiro, oriundas da segregação do híbrido SE 1055 F1, desenvolvido para condições quentes e úmidas, com resistência a Fusarium oxysporum f.sp. lycopersici race 2, a tomato mosaic virus (ToMV), a Verticilium dahliae e geminivirus (TYLCV), além das testemunhas cultivar Yoshimatsu e o próprio híbrido SE 1055 F1. O delineamento experimental adotado foi em blocos ao acaso, com 22 tratamentos, quatro repetições e parcela útil com duas plantas. Foram avaliados o número total de frutos por planta (NTF/PL), pegamento de frutos (PEG), massa de frutos não comerciais por planta (MFNC/PL), massa de frutos comerciais por planta (MFC/PL) e rendimento de frutos comerciais (REND). Em casa de vegetação foram registradas maiores temperaturas e menor luminosidade em relação ao cultivo no campo. As linhagens 08, 12 e 13 apresentaram maior pegamento de frutos em casa de vegetação, mostrando-se mais indicadas para o cultivo em temperaturas elevadas. No campo, as linhagens 06 e 08 se destacaram na produção de frutos comerciais, não diferindo da 'Yoshimatsu'. Observaram-se em relação à média geral dos ambientes, maiores PEG e MFC/PL das linhagens quando estas foram conduzidas no cultivo em campo.
Keywords: Solanum lycopersicum; breeding; fruit set; Solanum lycopersicum; Melhoramento genético; Pegamento de frutos